Tuberculosis and the sexual and reproductive lives of women in Bangladesh. - Mrittika Barua; Francien Van Driel; Willy Jansen (PLoS ONE, 2018)
When they do not meet norms related to sexuality and reproduction, Bangladeshi women often face abandonment and are thus deprived of an active sexual life, a marital relationship, and motherhood. Little is known about how a stigmatised disease such as tuberculosis (TB) may constrain the reproductive health and sexual lives of women. This article, derived from a larger study on the impact of TB on women's sexual and reproductive health and rights in Narsingdi district and Dhaka, Bangladesh, aims to fill this gap. Based on interviews with nine married women who have or had TB, four husbands, and two mothers-in-law, this article highlights that the ways in which TB impedes on the sexual and reproductive lives of women depends on the stigma within their family and community, their relationships with their husbands, motherhood, their living arrangements, their economic contribution to the family and/or their disclosure of their TB diagnosis. Women with children and supportive husbands retain a stronger position among their in-laws and are less likely to be isolated or rejected. The patients' narratives revealed that the instructions of health workers influenced their decisions about intercourse or abstinence. Future studies should examine the instructions patients receive from health workers regarding their living and sleeping arrangements, sexual intercourse, and pregnancy, as well as policy documents on TB treatment and prevention.